Self-Assembly in Fuel Cells - Zhang, J.; Jiang, San Ping (2017)
© 2017 Elsevier Ltd. All rights reserved. Proton exchange membrane fuel cell (PEMFC) is an electrochemical energy conversion technology to directly convert the chemical energy of fuels to electricity with high efficiency and low greenhouse gas emission. As one of the most effective synthetic tools, self-assembly technology provides a simple and facile way to develop effective and durable proton exchange membranes and electrocatalysts for PEMFC with unique microstructure and properties. The emphasis of this article is on the mechanism, principle, and application of self-assembly techniques in the development and synthesis of key materials of PEMFCs, and latest development of inorganic PEM based on functionalized mesoporous silica is also introduced.